Apakah Beragama Membuat Bahagia? Meta-Analisis - Ghufron, M Nur; Suminta, Rini Risnawita (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2018)
This Study was meta-analysis of the correlation between religion and happiness. Meta-analysis aims at concluding, integrating, and interpreting data gathered from previous research. Therefore, apart from acting as primary research, the data to be analyzed through this method must have the same constructs and correlation patterns so that it could be compared with one another. The quantitative review includes 15 studies from 9 articles that contained a combined sample of approximately 7272. This analysis extends previous work by directly correcting error of sampling and measurements. Summary analysis provided support that religion has a correlation on happiness. The result showed religion have been identified as predictors and happiness.